Implementación de un sistema de contabilidad comercial para el comisariato “kerly” del cantón la maná, provincia de Cotopaxi, periodo 1ro. de septiembre al 30 de noviembre del 2009 - Guilcaso Camalle, Eduardo Patricio (2010)
The accounts remain an important tool for the growth of small and large companies can get classified information on all economic movements at any time will be needed for decision-making was therefore necessary to implement an accounting system Business in the Commissariat “Kerly”. In field research conducted found that Commissariat “Kerly” does not have accounting records due to lack of training of accounting and tax rules that allow information processing activities. For our research study used a questionnaire that was addressed to the owners, employees, suppliers and customers of the commissary. The results highlights that do not use an accounting system to improve the activities, has not been properly trained personnel working in the area, to take advantage of best human resources available. With the information obtained and recommended, the company must implement the System of Double Entry Accounting, which facilitates the processing of data and records of all financial transactions that were generated in the development of their activities. The result of the information is accurate, relevant and timely decision making and fulfillment of all obligations, what activities will improve, control and use resources efficiently, offering higher returns remain favorable and beneficial to homeowners.